Pulmonary Embolism with Vertebral Augmentation Procedures - Swetha Bopparaju; Joseph Varon; Salim Surani (Case Reports in Pulmonology, 2013)
With the prevalence of an aging American population on the rise, osteoporotic vertebral fractures are becoming a common occurrence, resulting in an increase in vertebral augmentation procedures and associated complications such as cement leakage, vertebral compressions, and pulmonary embolism. We describe a patient who presented with respiratory distress three years following kyphoplasty of the lumbar vertebra. Computed tomography (CT) angiogram of the chest confirmed the presence of polymethylmethacrylate (PMMA) cement in the lung fields and pulmonary vessels. We conducted a systematic review of the published literature identifying effective management strategies for the treatment of vertebroplasty-associated pulmonary embolism.